ANALYSIS OF THE INSTALLATION METHOD OF HALF SLAB PRECAST ON KARANG SINGA BEACON TOWER BUILDING - AHMAD MAHIRUL ILMI; Anisa Carina; Agus Setiawan; Mochammad Qomaruddin (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2025)
ABSTRACT Innovation in construction methods is increasingly needed, especially in projects in extreme geographical conditions. This study analyzes the effectiveness of the precast half slab installation method in the Liang Liang Coral Beacon Tower Construction project in the Riau Islands, which is located ±4 nautical miles from Bintan Island, so that it does not allow the application of conventional casting. The half slab precast method was chosen to overcome the limitations of the working area, weather risks, and the need to accelerate construction time. The analysis was carried out through the stages of half slab design planning, fabrication, material distribution using a service barge, to the erection process using a crawler crane. The technical data of the half slab includes the configuration of HS1, HS2, and HS3 with a thickness of 200 mm and a concrete topping of 150 mm. The results of the analysis showed that the precast half slab met the technical requirements based on SNI 2847:2013 and the PCI Design Handbook, both in terms of lifting load capacity, bending moment control, and deformation during installation. The installation method has also proven to be efficient in terms of time and cost because it minimizes the use of formwork, reduces the risk of wet work at sea, and accelerates the implementation of erections. This study concludes that the half slab precast method is an effective and efficient solution for floor structure work in offshore projects, especially in locations with limited access and challenging environmental conditions.